Acute retinal hemorrhage after Pipeline embolization device placement for treatment of ophthalmic segment aneurysm: A case report. Issue 4 (August 2018) - Adeeb, Nimer; Moore, Justin; Griessenauer, Christoph J; Gupta, Raghav; Fazelat, Ahad A; Ogilvy, Christopher S; Thomas, Ajith J
Introduction: Ophthalmic segment aneurysms may present with visual symptoms due to direct compression of the optic nerve. Treatment of these aneurysms with the Pipeline embolization device (PED) often results in visual improvement. Flow diversion, however, has also been associated with occlusion of the ophthalmic artery and visual deficits in a small subset of cases. Case report: A 49-year-old Caucasian female presented with subarachnoid hemorrhage due to a ruptured anterior communicating artery aneurysm. On follow-up imaging, the patient was found to have a right asymptomatic ophthalmic segment aneurysm. Due to the irregular shape of the aneurysm and history of aneurysmal subarachnoid hemorrhage, the decision was made to treat the aneurysm with a PED. Postoperatively, the patient complained of floaters in the right eye. Detailed ophthalmologic examination showed retinal hemorrhage and cotton-wool spots on the macula. Such complication after PED placement has never been reported in the literature. Conclusion: Visual complications after PED placement for treatment of ophthalmic segment aneurysms are rare. It is thought that even in cases where the ophthalmic artery occludes, patients remain asymptomatic due to the rich collateral supply from the external carotid artery branches. Here we report a patient who developed an acute retinal hemorrhage after PED placement.